PRODUKSI DAN EFEKTIVITAS MOTION GRAPHIC SEBAGAI MEDIA PROMOSI ZETIZEN BATAM POS - Fujianto, Rahmat Zainur; Antoni, Condra (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2020)
Nowadays, the promotional media is increasingly growing. This can be seen from the number of companies that do promotions and to be known by the public. Zetizen Batam Pos is a tool for teenagers between 13 to 20 years old that provides the information about lifestyle and daily life, through various media such as printed media, online media, and other various offline activities. The problems that were found are some people do not know much about Zetizen Batam Pos. Therefore, Zetizen Batam Pos needs more attractive, creative and effective promotional media such as motion graphics.This study uses the Villamil-Molina (1997) development method which consists of five stages: development, pre-production, production, post-production, and delivery. Softwares used in this study are Adobe Illustrator CC 2017, Adobe After Effects CC 2017, and Adobe Premiere Pro CC 2017. After the motion graphic had been completed, an EPIC model analysis was conducted to test the motion graphic’s effectiveness as a promotional media for Zetizen Batam Pos. There are four dimensions of EPIC such as Empathy, Persuasion, Impact, dan Communication. Testing the effectiveness of Zetizen Batam Pos's motion graphics by using the EPIC model is very effective because the results for the dimension of Empathy, Persuasion, Impact, and Communication are 4.38, 4.37, 4.52, and 4.59 respectively. In that case, the communication dimension is becoming the most dominant of all dimensions. This could happen because the display of motion graphics on Zetizen Batam Pos can deliver the right, clear, and understandable information to the audience.